Progressivism In The Elementary School Curriculum: A Systematic Literature Review - Unga Utami; Unga Utari (Berpusi Publishing, 2023)
Progressivism is one of the schools of modern educational philosophy which is based on changes in the implementation of education for the better. Progressivism requires the basics of education that are meaningful for every student. The of progressivism refers to the implementation of education that is carried out by involving an active and centered role for students. The of progressivism that sided with students became one of the philosophical foundations in the development of the education curriculum in Indonesia, including education at the elementary school level. Curriculum changes took place in 2013 following the direction and policies of the government. This curriculum was introduced with the term